Post-traumatic Stress Disorder Symptoms Resulting from Torture and Other Traumatic Events among Syrian Kurdish Refugees in Kurdistan Region, Iraq - Ibrahim, Hawkar; Hassan, Chiya Q. (Frontiers in Psychology, 2017)
Political violence is known to cause psychological distress. There is a large body of empirical studies drawing correlations between war trauma, torture and posttraumatic stress disorder (PTSD). However, there are few studies on the effects of war-related trauma among Syrian refugees after events following the ‘Arab Spring’ uprisings between 2010 and 2012. This study examines the association of PTSD symptoms with torture and other traumatic events among Syrian Kurdish refugees living in Kurdistan Region, Iraq. The experiences and PTSD symptoms among 91 Syrian Kurdish refugees in the Arbat camp in the Sulaymaniyah Governorate of the Kurdistan Region of Iraq were assessed using the Harvard Trauma Questionnaire (HTQ), sections I, IV and V. Results showed that the estimated levels of PTSD symptoms were high: between 35% and 38%. There were no significant gender differences in the occurrence of PTSD symptoms. However, men reported significantly more general traumatic experiences than women. There were significant positive correlations between PTSD symptoms with traumatic events and torture (r = .500, r = .366 respectively). Examining the mental health impact of torture and other traumatic events among refugees has possible implications for organizations managing rehabilitation programs for individuals who have been exposed to traumatic events.